مكتبات كليات و معاهد هيئة التعليم التقني في الموصل : دراسة تحليلية على وفق معايير الجودة - بديعة يوسف عبدالرحمن; أمثال شهاب احمد (PROSPECTIVE RESEARCHES, 2023)
The research aims at showing the extent of applying quality criteria in the libraries of college and institutes in the technical teaching organization, depending on a research (the directory guide for quality criteria application in the institutions of higher education. Research prepared by Samir Kamil Alkhateeb 2010). The was conducted to show the weak and potential aspects of daily work in library in accordance with there criteria. Inaddition, the research tries to show strength and weakness points in the daily work in the libraries of the Technical Teaching institute and as follows: technical college\ Mosul, Technical institute Ninaveh, administrative technical college\ Teachnical institute Mosul. The research comes up with a set of conclusion, such as: First, there is a limited number of specialists and non- specialists in the staff members. Second, No description is given for the employee of libraries. Thired, computers are not uitilized there. Finally, all libraries expect the library of Administrative Technical College; don’t provide the facility of using internet.